2003
DOI: 10.1128/jvi.77.17.9173-9182.2003
|View full text |Cite
|
Sign up to set email alerts
|

Tsg101 Control of Human Immunodeficiency Virus Type 1 Gag Trafficking and Release

Abstract: The structural precursor polyprotein of human immunodeficiency virus type 1, Pr55 gag , contains a prolinerich motif (PTAP) called the "late domain" in its C-terminal p6 region that directs release of mature virus-like particles (VLPs) from the plasma membranes of gag-transfected COS-1 cells. The motif binds Tsg101 (vacuolar protein-sorting protein 23, or Vps23), which functions in endocytic trafficking. Here, we show that accumulation of the wild-type (wt) Gag precursor in a fraction of COS-1 cytoplasm enrich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
78
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 55 publications
(73 reference statements)
11
78
0
Order By: Relevance
“…Interestingly, we observed that retroviral particle release was significantly less efficient in HeLa cells than in 293T, suggesting that there is a strong relationship between the ability of Gag to traffic through the endocytic pathway and the efficiency of virus particle release. Consistent with our present observations, other retroviral Gag proteins have been found to be associated with endocytic compartments (Basyuk et al, 2003;Goff et al, 2003;Sfakianos and Hunter, 2003). Recent studies also demonstrated that retroviral particles can assemble and bud in intracellular compartments in various cell types (Nydegger et al, 2003;Sherer et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, we observed that retroviral particle release was significantly less efficient in HeLa cells than in 293T, suggesting that there is a strong relationship between the ability of Gag to traffic through the endocytic pathway and the efficiency of virus particle release. Consistent with our present observations, other retroviral Gag proteins have been found to be associated with endocytic compartments (Basyuk et al, 2003;Goff et al, 2003;Sfakianos and Hunter, 2003). Recent studies also demonstrated that retroviral particles can assemble and bud in intracellular compartments in various cell types (Nydegger et al, 2003;Sherer et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, monoubiquitination of viral matrix proteins has been postulated to promote efficient release of virus and/or VLPs (36,38,39,(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59).…”
mentioning
confidence: 99%
“…by arresting the release of viral particles from the plasma membrane of host cells (12,20). Furthermore, mutations in motifs of either TSG101 or Gag that are essential for the interaction of these proteins also reduce the production of infectious viral particles (12,13).…”
mentioning
confidence: 99%